2009
DOI: 10.1007/s12070-009-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of otological manifestations in children with cleft palate

Abstract: Aims i) To determine the prevalence of the various otological manifestations that occured in children aged between 1 to 5 years, presenting to the Departments of ENT and Plastic Surgery with overt cleft palate. ii) To evaluate the possibility of the association of the different otological manifestations in relation to the various types of cleft. Results Prevalence of external ear abnormalities in the studied population was 13%. More than 55% of the participants' ears were diagnosed clinically with OME. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
2
10
0
Order By: Relevance
“…This is higher than that noted in previous studies which have reported the incidence of cholesteatoma in 1-5.9%. 12,13,16,17 Findings of this study are in concordance with earlier studies which reported hearing loss to be a common feature in CLP patients. 7,9,12,13,17,18 Fifty five percent of CLP patients had conductive hearing loss which varied from mild to moderately severe with mild hearing loss being the commonest.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is higher than that noted in previous studies which have reported the incidence of cholesteatoma in 1-5.9%. 12,13,16,17 Findings of this study are in concordance with earlier studies which reported hearing loss to be a common feature in CLP patients. 7,9,12,13,17,18 Fifty five percent of CLP patients had conductive hearing loss which varied from mild to moderately severe with mild hearing loss being the commonest.…”
Section: Discussionsupporting
confidence: 91%
“…CLP is reported to have male preponderance with male to female ratio being 2:1. 13,15 The same was observed in this study too with the male to female ratio being 2.1:1.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, otoscopy was used as a test of tympanic membrane appearance and mobility. Moreover, it is insurmountable to go the route of subjective hearing assessment test like pure tone audiometry in subjects of this age group [16]. However, a working idea of child's auditory status can be obtained by bringing objective hearing tests into play.…”
Section: Discussionmentioning
confidence: 99%